Investigating donor fulfillment in global climate finance: the role of EU commitment - Nor, Mohamed Ibrahim (Frontiers in Climate, 2025)
This study investigates key determinants influencing donor fulfillment rates (DFR) in the context of global climate finance. Using panel data analysis, the study examines the impact of pledged and deposited funds, EU membership, and fund type on donor fulfillment. The Random Effects model was validated through a Hausman test and used to interpret the main results. The analysis reveals that higher pledged amounts are significantly associated with lower fulfillment rates, while actual deposited funds positively and strongly affect DFR. EU membership consistently improves donor fulfillment, suggesting that institutional alignment matters, whereas fund type showed no significant influence in the RE model. The findings suggest a need for more realistic pledging practices, stronger monitoring and accountability mechanisms, and institutional frameworks that promote follow-through on financial commitments. This study introduces a novel empirical variable—EU membership—to assess how regional affiliation influences donor behavior. This study offers a new lens to evaluate the effectiveness of international climate finance commitments. The research advances the Principal–Agent Theory, Institutional Theory, and Rational Choice Theory to explain donor behavior. It fills a critical gap in empirical literature by distinguishing between the effects of pledges versus actual deposits, highlighting the role of regional institutional contexts.